The Effect of Lemon Aromatherapy on Emesis in 1st Trimester Pregnant Women: Pengaruh Aromaterapi Lemon Terhadap Emesis pada Ibu Hamil Trimester 1 - Rizqiah, Agni Saila; Dinengsih, Sri; Kundaryanti, Rini (Universitas Muhammadiyah Sidoarjo, 2023)
Pregnant women usually suffer from nausea and vomiting in the first months of pregnancy, Treatment of nausea and vomiting can be done by pharmacological and nonpharmacological methods. Pharmacological therapy can be done by giving vitamin B6, and non-drug therapy can be done by giving lemon aromatherapy. to overcome the symptoms of nausea and vomiting, Objective: to determine how lemon aromatherapy affects vomiting in first trimester pregnant women at TPMB N Bogor City. Methodology: this study used a quasi experiment with a pretest-posttest design with control. The population was from pregnant women who experienced vomiting during 1st trimester pregnancy at TPMB N Bogor City, conducted in July 2023. The sample was 26 people. The instrument used the pregnancy uniqiue quantification of emesis and nausea (PUQE) questionnaire. Results:The mean emesis score before lemon aromatherapy was 7.00, while after lemon aromatherapy the mean score was 0.00, for a mean difference of 7.00.and a p-value of 0.001. The average score of emesis gravidarum before being given vitamin B6 is 6.50 and the average score of emesis after taking vitamin B6 is 0.00 with a mean difference of 6.50 with a p-value of 0.002. Conclusion:There is a decrease in the score of emesis gravidarum given Lemon Aromatherapy in first trimester pregnant women in TPMB N Bogor City, but in the control group it is not as significant as in the intervention group.Suggestion: It is recommended that mothers who experience nausea and vomiting can use lemon aromatherapy as a way to reduce complaints of emesis gravidarum.